Gene-specific signal transduction between microtubules and tubulin genes in Tetrahymena thermophila. - Gu, L (1995)
Mammalian cells regulate tubulin mRNA abundance by a posttranscriptional mechanism dependent on the concentration of tubulin monomer. Treatment of mammalian cells with microtubule-depolymerizing drugs and microtubule-polymerizing drugs causes decreases and increases in tubulin mRNA, respectively (D. W. Cleveland, Curr. Opin. Cell Biol. 1:10-14, 1989). In striking contrast to the case with mammalian cells, perturbation of microtubules in Tetrahymena thermophila by microtubule-depolymerizing or -polymerizing drugs increases the level of the single alpha-tubulin gene message by increasing transcription (L. A. Stargell, D. P. Heruth, J. Gaertig, and M. A. Gorovsky, Mol. Cell. Biol. 12:1443-1450, 1992). In this report we show that antimicrotubule drugs preferentially induce the expression of one of two beta-tubulin genes (BTU1) in T. thermophila. In contrast, deciliation induces expression of both beta-tubulin genes. Tubulin gene expression was examined in a mutant strain created by transformation with an in vitro-mutagenized beta-tubulin gene that conferred resistance to microtubule-depolymerizing drugs and sensitivity to the polymerizing drug taxol and in a strain containing a nitrosoguanidine-induced mutation in the single alpha-tubulin gene that conferred the same pattern of drug sensitivities. In both cases the levels of tubulin mRNA expression from the drug-inducible BTU1 gene in the mutant cells paralleled the altered growth sensitivities to microtubule drugs. These studies demonstrate that T. thermophila has distinct, gene-specific mechanisms for modulating tubulin gene expression depending on whether ciliary or cytoplasmic microtubules are involved. They also show that the cytoplasmic microtubule cytoskeleton itself participates in a signal transduction pathway that regulates specific tubulin gene transcription in T. thermophila.